2014
DOI: 10.1159/000365277
|View full text |Cite
|
Sign up to set email alerts
|

Bispectral Index and Lower Margin Amplitude of the Amplitude-Integrated Electroencephalogram in Neonates

Abstract: Background: The lower margin amplitude (LMA) of the amplitude-integrated electroencephalogram (aEEG) is suppressed in neonates during deep sedation, a feature that is attributed to the bispectral index (BIS) in adults. Objective: We compare the BIS and the LMA of the aEEG in neonates. Methods: Thirty neurologically healthy neonates between 37 and 44 weeks postmenstrual age were included in this study. Twenty patients received sedoanalgesic therapy for various reasons. BIS and aEEG recordings were performed sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…aEEG can sensitively reflect the change of brain physiology at the early stage of brain ischemic hypoxia. This is the only way to detect subclinical seizures and reversible changes of brain function [ 23 , 24 ]. Some authors [ 25 ] indicated that aEEG can confirm encephalopathy within 6 h after HIE.…”
Section: Discussionmentioning
confidence: 99%
“…aEEG can sensitively reflect the change of brain physiology at the early stage of brain ischemic hypoxia. This is the only way to detect subclinical seizures and reversible changes of brain function [ 23 , 24 ]. Some authors [ 25 ] indicated that aEEG can confirm encephalopathy within 6 h after HIE.…”
Section: Discussionmentioning
confidence: 99%
“…42 The mean BIS values considering all three groups were considerably lower than the more appropriate cutoff values proposed by Lamas et al 30 Even if the BIS is prone to change when higher doses of sedative and analgesic drugs are administered, this method does not add more information than the aEEG already does (Figure 1). 43 As already concluded by Kissin,44 when the BIS is used for a new drug or a new population it must revalidated because changes in the basic algorithm of this method could occur.…”
Section: P-value (95% Ci) Light Vs Deep Sedationmentioning
confidence: 99%
“…[1] Most of the drugs that are frequently used in the paediatric population affect the characteristics of the electroencephalogram (EEG), and several calculated EEG parameters have been used to monitor the depth of anaesthesia in both children [2][3][4] and neonates. [5] The amplitudeintegrated EEG (aEEG) is a bedside monitoring tool widely used in newborns to continuously monitor brain activity and detect seizures. [6,7] Following neonatal encephalopathy, the degree and timing of aEEG voltage depression and aEEG recovery also predicts outcome after perinatal asphyxia in both cooled and non-cooled newborns.…”
Section: Introductionmentioning
confidence: 99%